Radicals : audacious writings by American women, 1830-1930. - Stabel, Meredith, 1992-; Turpin, Zachary (University of Iowa Press, 2021)
"Smoking. Pauline Hopkins on alchemy and the undead. Frances E.W. Harper on woman's political future. Sui Sin Far on cross-dressing. Emma Lazarus and Angelina Weld Grimke on lesbian longing. Julia Ward Howe on intersexuality. Charlotte Perkins Gilman on euthanasia. Emma Goldman against the tyranny of marriage. Ida B. Wells against lynching. Anna Julia Cooper on Black American womanho. Frances Willard on riding a bicycle. This anthology is perhaps the first of its kind: a full-length collection of radical writings by American women of the 19th and early 20th century, with all major genres represented-fiction, poetry, drama, memoir, essays, and oratory-and voices of color prioritized. Many of these writings have never been anthologized before; some have never even been reprinted before. Stabel and Turpin endeavor to counterbalance widely canonized voices with a greater proportion of writings by less-anthologized Black feminists, Native feminists, and Asian American feminists, many of whom were writing for their lives and the lives of their families and communities, often at the risk of being harassed, slandered, disenfranchised, or lynched. Readers will find the original version of what was later edited into Sojourner Truth's "Ain't I a Woman?" speech, Julia A.J. Foote's account of her fight to be able to preach in the A.M.E. Church despite being a woman, and Julia Ward Howe's sensitive treatment of intersex life in America. They will also encounter new and surprising facets of the authors they know and love. For example, Emily Dickinson's most overtly erotic poems, those usually passed over in favor of other verses that misleadingly suggest a celibacy or disinterest in sex on Dickinson's part; and Kate Chopin's "An Egyptian Cigarette," her first-person fictional account of smoking pot-originally published in Vogue. Readers will enjoy excerpts from Pauline Hopkins's Of One Blood, a novel of alchemy and the undead, as well as from Amelia E. Johnson's Clarence and Corinne, a traditional love story. Simply writing such works was a radical freedom that these women had to carve out for themselves, in an era when many of them were legally considered property, none could vote, and reading and writing were often seen as privileges only for the free and wealthy. Radicals is ultimately intended to undo silences and prioritize unheard, underrepresented, powerful works of literature-from a period whose later historians often relegated women's writings to the periphery of American culture. One and all, these were women of genius and audacity, and, as Adah Isaacs Menken writes of such radicals, "this very audacity is divine""--